Ҳусанбоев Садафбек (Scientific journal of the Fergana State University, 2023)
The article considers ways to improve the development of foreign and domestic tourism on the basis of further development of science and technology, effective use of tourism as an important factor of innovative development in Uzbekistan, ways to increase the potential of education and science in tourism, existing problems and solutions.